Your personalized internet - Harris, Duchess; Herschbach, Elisabeth (Harris, Duchess. News literacy., 2018)
Explores how the internet is personalized through the processing of analyzing user's algorithms. Highlights privacy issues related to the collection of data for algorithms. Includes text-related questions, a glossary, online resources, and color photographs.